Self-reported vaccination-related behavior patterns among healthcare workers and the association with self-directed learning frequency: A nationwide cross-sectional survey - Ma, Yuan; Han, Xuan; Li, Wei; Yang, Yuan; Xu, Yunshao; Liu, Di; Yang, Weizhong; Feng, Luzhao; Ma, Libing (Frontiers in Public Health, 2022)
Background: Healthcare workers play an essential role in improving the public’s vaccination uptake, but the full picture of such workers’ engagement in vaccination-related behaviors has not been appropriately identified. According to the Integrated Theory of Health Behavior Change, self-directed learning may be a promising intervention for fostering engagement in vaccination-related behaviors, but the association between self-directed learning and such behaviors remains unclear. This study aimed to determine Chinese healthcare workers’ level of engagement in behaviors for combatting vaccine-preventable diseases and assess the association between frequency of performing vaccine-focused SDL and engagement in vaccination-related behaviors. Materials and Methods: An online cross-sectional survey was conducted from January 27 to February 21, 2022, using the survey platform “wjx.” Respondents were restricted to healthcare workers aged 18–65 years. A Sankey diagram and bar plots were constructed to determine patterns of engagement in a vaccination-related-behavior chain. Unconditional binary logistic regression models were fitted to determine the association between frequency of performing vaccine-focused self-directed learning and engagement in vaccination-related behaviors. Results: Of the 2,248 survey respondents, data for 2,065 were analyzed. Participants who had received influenza or pneumococcal vaccination, routinely recommended vaccination to patients, tracked patients’ vaccination status, and recommended efficiently accounted for 43.2%, 50.8%, 40.3%, and 36.4% of the total participants respectively. When only considering those who routinely made such recommendations, the proportion of those who performed tracking and efficient recommendation was 28.8% and 26.2%, respectively. When compared to performing self-directed learning “never to less than once/six months,” performing self-directed learning “more than once/week” was positively associated with being vaccinated (OR, 95% CI: 2.30, 1.74–3.03), routinely recommending vaccination (OR, 95% CI: 4.46, 3.30–6.04), and tracking the status of patients so recommended (OR, 95% CI: 6.18, 4.35–8.76). Conclusions: Chinese healthcare workers’ pattern of engagement in vaccination-related behaviors must be improved. Higher frequencies of engagement in self-directed learning are associated with more active engagement in vaccination-related behaviors, meaning raising such frequencies could be a promising intervention for fostering behavior changes in this regard and ultimately increasing vaccination coverage.